The impact of training program using the ballistic exercises on the endurance strength of football players under 18 years of age - ملوك, كمال; بوشامة , فريد (sports creativity, 2025)
The study aims to identify the extent of the impact of a training program using ballistic exercises on the durability of strength for football players less than 18 years old. One of the objectives of the research is to develop a ballistic training program with rubber cords for the lower and upper limbs. For this purpose, we used the experimental approach on a sample of a team under 18 years old for the Tissemsilt Union team club. The 25 players were deliberately selected and divided into two groups, control and experimental. The training program lasted 10 weeks, with an average of two sessions per week. To collect data, we used pre-tests after collecting the results and processing them statistically. It was found that there were statistically significant differences between the control and experimental group in the post test and in favor of The experimental group, which indicates the effectiveness of the training program, and on this basis, the study recommended the necessity of working with ballistic exercises in training programs to develop the permanence of forc